Mucorales prevalence and azole-resistance surveillance on different indoor environments: a menace to be tackled - Viegas, Carla (2018)
Projeto ACT - Exposição profissional a fungos, micotoxinas e partículas na indústria da panificação (Projeto ACT_005DBB/12). Projeto IPL - Waste Workers' Exposure to Bioburden in the Truck Cab during Waste Management - W2E Bioburden (IPL/2016/W2E_ESTeSL). Projeto IPL - Bacterial Bioburden assessment in the context of occupational exposure and animal health of swine productions - BBIOR (IPL/2016/BBIOR_ESTeSL).